Black limestone used in antiquity: recognizing the limestone of Teos. (9th September 2018) - Brilli, M.; Giustini, F.; Kadıoğlu, M.
Abstract : This paper documents the petrographic and isotopic characteristics of some black limestones that were exploited in antiquity near the ancient site of Teos in Ionia (south‐western Anatolia, Turkey). The best‐quality black limestone of Teos is represented by a series of step‐cut‐shaped blocks situated north of the Seferihisar–Sığacık road, destined to be exported and used for architectural elements. The techniques used to study these blocks allow possible identification of the origin of Teos in ancient black stone artefacts. Nevertheless, petrographic and geochemical investigation on some black limestones that outcrop in the area near Teos has not firmly identified the quarry fronts from which these blocks were quarried away, but it supports the known hypothesis that Teian black limestones were found and quarried in conjunction with the Africano marble.